Bidirectional Neuro‐Immune Interactions of the Orexin/Hypocretin System: A Systematic Review With Conceptual Synthesis - Jean Claude Hakizimana; Zephyrin Izukwizabigenza; Marie Gorette Kampire; Joseph Mucumbitsi; Abdullateef Isiaka Alagbonsi (Clinical and Experimental Neuroimmunology, 2026)
ABSTRACT Background Beyond regulating sleep, the orexin/hypocretin system participates in bidirectional neuro‐immune interactions that may influence neurodegenerative diseases (NDs) and chronic inflammatory conditions. This systematic review aimed to conceptually synthesize evidence on these interactions and their clinical implications. Methods Following PRISMA 2020 guidelines, a comprehensive search was performed in PubMed, Embase, Web of Science, Scopus, and PsycINFO. Studies were included if they reported original empirical data (human, animal, or in vitro) examining orexin signaling in relation to cytokines, microglial activation, or neuroinflammation. Results Of 1248 records screened, 18 studies (three human, 13 animal, two in vitro/ex vivo) were included. Human studies, albeit limited, showed consistent suppression of the immune‐to‐orexin signaling: an 11‐fold increase in CD4 + T cells was observed specifically in the hypocretin region in NT1 brains; peripheral LPS reduced orexin neuron activity, and lower orexin‐A levels correlated with elevated pro‐inflammatory cytokines and worse cognitive/fatigue outcomes in epilepsy, depression, and Sjögren's syndrome. Conversely, preclinical studies showed that orexin‐to‐immune signaling demonstrated consistent anti‐inflammatory effects. Orexin‐A shifted microglia toward an anti‐inflammatory phenotype, inhibited key pathways (NF‐κB, ERK, NEK7/NLRP3), reduced cytokines (IL‐1β, IL‐6, TNF‐α), and attenuated astrogliosis across models of intracerebral hemorrhage, chronic hypoperfusion, sepsis‐associated encephalopathy, experimental autoimmune encephalomyelitis, and gut‐brain inflammation. Sex‐ and region‐specific effects were noted. Conclusion Inflammation generally suppresses orexin signaling, while orexin‐A signaling exerts predominantly anti‐inflammatory effects by modulating microglial phenotype and key inflammatory pathways. These bidirectional interactions highlight the orexin system as a potential bridge between sleep dysregulation and neuroinflammation. However, most evidence on orexin‐to‐immune signaling derives from preclinical models, and significant gaps remain in human mechanistic studies and clinical translation on immune‐to‐orexin signaling. Orexin receptor agonists warrant further investigation as candidate adjunctive therapies in neurodegenerative and chronic inflammatory conditions.